2020
DOI: 10.3988/jcn.2020.16.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum of Myelin Oligodendrocyte Glycoprotein-Immunoglobulin G-Associated Disease in Korean Children

Abstract: Background and Purpose The myelin oligodendrocyte glycoprotein (MOG) antibody is detected at a high rate in childhood acquired demyelinating syndrome (ADS). This study aimed to determine the diagnostic value of the MOG antibody in ADS and the spectrum of MOGantibody-positive demyelinating diseases in children. Methods This study included 128 patients diagnosed with ADS (n=94) or unexplained encephalitis (n=34). The MOG antibody in serum was tested using an in-house live-cell-based immunofluorescence assay. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…MOG and anti-synaptic antibody testing were performed as described previously. 19,20 Medical records were reviewed retrospectively for age at onset, sex, clinical presentation, laboratory results including CSF profile, follow-up duration, relapse, treatment regimen, and outcome. Autoimmune encephalitis relapse was defined as any new or worsening neurological symptoms after at least 4 weeks of improvement or stabilization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MOG and anti-synaptic antibody testing were performed as described previously. 19,20 Medical records were reviewed retrospectively for age at onset, sex, clinical presentation, laboratory results including CSF profile, follow-up duration, relapse, treatment regimen, and outcome. Autoimmune encephalitis relapse was defined as any new or worsening neurological symptoms after at least 4 weeks of improvement or stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…Among the patients included in the study, we investigated neuronal and glial antibodies including anti‐MOG, anti‐NMDAR, anti‐α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor, anti‐dipeptidyl peptidase‐like protein 6, anti‐leucine‐rich glioma‐inactivated 1, anti‐contactin‐associated protein‐like 2, anti‐γ‐aminobutyric acid type B receptor, and anti‐glutamic acid decarboxylase antibodies. MOG and anti‐synaptic antibody testing were performed as described previously 19,20 . Medical records were reviewed retrospectively for age at onset, sex, clinical presentation, laboratory results including CSF profile, follow‐up duration, relapse, treatment regimen, and outcome.…”
Section: Methodsmentioning
confidence: 99%
“…This general distribution of MOGAD phenotypes was also observed when assessing all identified studies (Table 1). Overall, 39 identified articles (including the six aforementioned incident cohort studies) reported the phenotype at initial presentation for 1,686 pediatric MOGAD patients 4–6,8,11–45 . Most of these studies were limited by the potential for selection bias in patient identification (e.g., patients with stored serum available for retrospective MOG‐Ab testing, relapsing disease course, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that approximately 40% of children with ADEM and nearly 100% of children with multiphasic disseminated encephalomyelitis (MDEM) were seropositive for MOG-IgG ( 10 ). Previous studies have reported the clinical and neuroradiological characteristics of pediatric ADEM with MOG-IgG ( 11 14 ). The clinical and MRI characteristics of patients with ADEM with or without MOG-IgG in northern China have not been reported.…”
Section: Introductionmentioning
confidence: 99%